Comparison of different physical methods and preservatives for control of Fusarium proliferatum rot in garlic - La Placa, Laura; Giorni, Paola; Mondani, Letizia; Magan, Naresh; Battilani, Paola (MDPI, 2022)
Dry rot is an emerging issue for garlic production worldwide and Fusarium proliferatum is its major causal agent. Since the disease is seed-transmitted, sowing healthy cloves is crucial. In this study, some disinfection strategies were tested on garlic seeds, including steam, dry heat, chemical disinfectants and gaseous ozone (O3). Steam reduced the Colony Forming Units·g−1 (CFUs·g−1) by up to 92% in garlic seeds, but, at the same time, it affected their germination (−36%). Similarly, hydrogen peroxide (H2O2) and peracetic acid (C2H4O3) reduced the CFUs·g−1 by up to 83%; however, these methods also severely impaired germination (−40%). Dry heat did not negatively impact germination, but fungal contamination was not significantly reduced. The most promising strategy was gaseous O3 treatment; it decreased CFUs·g−1 by up to 96%, without causing any reduction of germination. The treatments applied were partially effective because the fungus is predominantly located in the outer layer of the seed, although it is also found in the inner portions. Some of these treatments can contribute to garlic protection from seed-borne pathogens and possibly reduce the occurrence of garlic dry rot.
Keywords: Fusarium proliferatum; garlic; dry rot; physical methods; preservatives